2010
DOI: 10.1093/europace/euq042
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of atrial electrophysiology induced by electrolyte variations: combined computational and P-wave analysis

Abstract: Changes of plasma ionic concentrations may lead to modifications of atrial electrophysiology that can favour AF onset, namely a decrease of atrial CV and a decrease of atrial ERP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 41 publications
6
31
0
1
Order By: Relevance
“…This phenomenon has been interpreted as a sign of intra-atrial conduction slowing. Moreover, the frequent occurrence of supraventricular ectopic beats during haemodialysis sessions may trigger AF episodes in a situation that is already highly favorable for the onset of arrhythmias [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon has been interpreted as a sign of intra-atrial conduction slowing. Moreover, the frequent occurrence of supraventricular ectopic beats during haemodialysis sessions may trigger AF episodes in a situation that is already highly favorable for the onset of arrhythmias [22].…”
Section: Discussionmentioning
confidence: 99%
“…[3] End stage renal disease patients incur into sudden changes in plasma electrolyte concentrations during the haemodialysis session probably resulting in changes in the myocardial cells' action potential [23]. For this reason, haemodialysis represents a unique human model to test in vivo the effects of rapid changes in plasma electrolytes and the analysis of acute electrocardiographic alterations induced by haemodialysis may contribute to clarify the mechanisms involved in the genesis of cardiac arrhythmias [22]. QT dispersion (maximum minus minimum QTc interval on a standard 12-lead electrocardiogram) is also taken as a risk factor for ventricular arrhythmias and sudden death [12].…”
Section: Discussionmentioning
confidence: 99%
“…42 In the study of Maebuchi et al, 43 even after controlling for age, sex, hypertension, ECG abnormalities, dyslipidemia, diabetes, obesity, serum calcium and potassium, alcohol intake, and smoking habits, the brachial-ankle PWV was shown to be independently associated with electrocardiographic QT interval prolongation. Moreover, in the report by Dart et al, 44 femoral-dorsalis pedis artery PWV was shown to be dependent on sex and potassium excretion.…”
Section: Variablesmentioning
confidence: 94%
“…[9][10][11][12][13] Brze izmene elektrolita (kalijum, kalcijum) u serumu za posledicu imaju poremećaj repolarizacije miokarda, povećanje disperzije P talasa (Pd ≥ 36 ms) i QT intervala (QTd ≥ 50 ms) i povećan rizik za nastanak pretkomorskih (paroksizmalna fibrilacija pretkomora), komorskih poremećaja srčanog ritma i iznenadne srčane smrti. [11][12][13][14][15][16][17][18] Hronične posledice intradijalizne hipotenzije Standardna hemodijaliza, sama po sebi, ima potencijal da izaziva ishemiju i reperfuziju miokarda i mozga. [19][20][21][22][23][24][25] Ishemijski događaji koji se ponavljaju izazivaju ošamućenje miokarda, razvoj sistolne srčane slabosti i iznenadne srčane smrti.…”
Section: Kliničke Posledice Intradijalizne Hipotenzijeunclassified